MEWUJUDKAN ENTREPENEUR EDUKATIF: STRATEGI PENYUSUNAN BUSINESS PLAN BAGI MAHASISWA FKIP UNIVERSITAS JAMBI - Novia Sri Dwijayanti; Iwan Putra; Arpizal arpizal; Hidayati hidayati; Dwi Rayana Siregar (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTThe progress of the digital era requires university graduates, including students from the Faculty of Education and Teacher Training (FKIP), to possess not only pedagogical competence but also entrepreneurial skills. However, the reality shows that the majority of FKIP students still face limitations in systematically formulating and implementing business ideas. This research aims to analyze effective business plan development strategies in realizing educational entrepreneurship within the Faculty of Education and Teacher Training (FKIP) at Jambi University. The research method applied is a descriptive qualitative approach using observation, interviews, and document analysis of entrepreneurship training participants and their supervising lecturers. The research findings indicate that students' understanding of business plan components significantly improved after receiving project-based and case study guidance. Collaborative learning strategies, the integration of entrepreneurship theory into education, and the utilization of digital technology are key factors supporting the program's success. The conclusion of this study confirms that developing a focused and contextual business plan can cultivate innovative, independent, and education-problem-solving-oriented educational entrepreneurial characters. This finding is expected to serve as the basis for developing an entrepreneurship curriculum at FKIP, which aims to cultivate future educators with an entrepreneurial spirit.Keywords: entrepreneur edukatif, business plan, FKIP Students ABSTRAKKemajuan era digital mengharuskan lulusan universitas, termasuk mahasiswa Fakultas Keguruan dan Ilmu Pendidikan (FKIP), untuk memiliki kompetensi tidak hanya dalam pedagogi tetapi juga dalam keterampilan kewirausahaan. Namun, kenyataannya menunjukkan bahwa mayoritas mahasiswa FKIP masih mengalami keterbatasan dalam merumuskan dan menerapkan ide bisnis secara sistematis. Penelitian ini bertujuan untuk menganalisis strategi penyusunan rencana bisnis yang efektif dalam mewujudkan kewirausahaan edukatif di lingkungan FKIP Universitas Jambi. Metode penelitian yang diterapkan adalah pendekatan deskriptif kualitatif melalui observasi, wawancara, dan analisis dokumen terhadap mahasiswa peserta pelatihan kewirausahaan serta dosen pembimbing. Temuan penelitian menunjukkan bahwa pemahaman siswa tentang komponen rencana bisnis meningkat secara signifikan setelah menerima bimbingan berbasis proyek dan studi kasus. Strategi pembelajaran kolaboratif, integrasi teori kewirausahaan dalam pendidikan, dan pemanfaatan teknologi digital merupakan faktor utama yang mendukung keberhasilan program. Kesimpulan penelitian ini menegaskan bahwa penyusunan business plan yang terarah dan kontekstual dapat membentuk karakter entrepreneur edukatif yang inovatif, mandiri, dan berfokus pada pemecahan masalah pendidikan. Temuan ini diharapkan dapat menjadi dasar pengembangan kurikulum kewirausahaan di FKIP, yang bertujuan untuk menumbuhkan calon pendidik dengan jiwa kewirausahaan.Kata Kunci: Entrepeneur edukatif, business plan, mahasiswa FKIP